Radioactive glassy inclusions in the soil sampled at the “Taiga” peaceful underground nuclear explosions site (the Perm region, Russia) - V. P. Ramzaev; V. S. Repin (Радиационная гигиена)
Activities of gamma-emitting radionuclides were measured in glassy inclusions (particles) found in soil samples from the “Taiga” peaceful nuclear explosions site (the Perm region, Russia). The measurements were performed using a stationary semiconductor gamma spectrometer. Activity concentrations were determined for the following technogenic radionuclides: 60Co, 94Nb, 137Cs, 152Eu, 154Eu, 155Eu, and 241Am. The activity concentrations of 241Am in the glassy inclusions were one to two orders of magnitude higher compared to the level of minimum significant activity concentration (1 Bq/g for 241Am) established by the Russian Radiation Safety Standards “NRB-99/2009”. Earlier, exceeding this level for the 241Am activity concentration in the native (unfractionated) soil samples from the “Taiga” site was reported by other researchers. In accordance with current Russian legislative and regulatory provisions regarding use of nuclear charges for peaceful purposes, the soil and radioactive glassy inclusions found in the soil correspond to the category of special radioactive waste. Considering the long half-life of 241Am (432 years), radiologically significant contamination by this radionuclide will persist at the “Taiga” site for the foreseeable future.